2019
DOI: 10.5001/omj.2019.76
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Omani Women with Breast Cancer-associated Brain Metastases Experience from a University Hospital

Abstract: ObjectivesBreast cancer (BC) is the leading cancer among women. Almost 20% of patients develop brain metastases (BM) and die shortly afterward. There is a dearth of data on the survival outcome of BC patients with BM from the Arab world.MethodsConsecutive women diagnosed with BC who developed radiologically-confirmed BM during their illness were identified through the hospital’s electronic patient’s records. Clinicopathological features and treatment outcomes were recorded. Survival was calculated using the Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Looking at original papers published from the five countries between 2011 and 2021, most analyzed datasets were of patients diagnosed before 2000 and up to the year 2012 [10,13,22,40,41,[66][67][68][69], and one meta-analysis looking at survival rates in patients with BC from the Eastern Mediterranean region included data within the same timeframe [70]. Only a couple papers reported outcome data up to year 2015 [71,72] with the absence of any outcome data from the region thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at original papers published from the five countries between 2011 and 2021, most analyzed datasets were of patients diagnosed before 2000 and up to the year 2012 [10,13,22,40,41,[66][67][68][69], and one meta-analysis looking at survival rates in patients with BC from the Eastern Mediterranean region included data within the same timeframe [70]. Only a couple papers reported outcome data up to year 2015 [71,72] with the absence of any outcome data from the region thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Most breast cancer cases were detected at advanced stages, similar to the trend reported from the Middle Eastern countries such as Oman. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Brain metastasis is a significant factor in the decline of overall survival (OS) and degradation of the quality of life in breast cancer patients. Studies have confirmed that 20% of breast cancer patients die of brain metastases [ 2 ]. Since most drugs cannot pass through the blood–brain barrier (BBB), chemotherapy alone has a limited effect [ 3 ]; additionally, brain metastases are mostly multiple foci, which makes them difficult to be controlled by surgery [ 4 ].…”
Section: Introductionmentioning
confidence: 99%